DNA functionalized plasmonic nanoassemblies as SERS sensors for environmental analysis. Issue 2 (24th September 2022) - Li, Jinxiang; Chen, Xueqin; Zhu, Jun‐Jie
Abstract: Surface‐enhanced Raman scattering (SERS) is among the most widely applied analytical techniques due to its easy execution and extreme sensitivity. Target molecules can be detected and distinguished based upon the fingerprint spectra that arise when absorbed on the SERS substrates surface, particularly on the SERS‐active hotspots. Thus, rational fabricating the enhancing substrates plays a key role in broadening SERS application. Programmable DNA functionalized plasmonic nanoassemblies, where DNA acts as both structure basis and functional unit, combine the specificity of DNA recognition, and modulate the assembly of plasmonic nanoparticles (NPs). Specifically designed DNA not only improves the selectivity to target molecules but also promotes the sensitivity of the optical signals through precisely regulating the distance between the molecule and the substrate. A variety of DNA‐functionalized SERS sensors have been reported and obtained well performance in the analysis of heavy metal ions in water, toxins, pesticide residues, antibiotics, hormones, illicit drugs, or other small molecules. This review places an emphasis on the design and sensing strategies of the DNA‐functionalized plasmonic nanoassemblies, as well as basic principles of Raman enhancement, and recent advances for environmental analysis. The current challenges and potential trends in the development of DNA‐functionalized SERS sensors for environmental pollutant monitoring in complicated scenarios are subsequently discussed. Abstract : This review places an emphasis on the introduction of the programmable DNA‐functionalized plasmonic nanoassemblies as SERS sensors for environmental analysis, where the specifically designed DNA acts as both structure basis and functional unit, combining the specificity of DNA recognition and the sensitivity of SERS detection via modulating the assembly of plasmonic nanoparticles.